Cytocompatibility, physical properties, and antibiofilm activity of endodontic sealers with amoxicillin - Andolfatto, Carolina [UNESP]; Bonetti-Filho, Idomeo [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Kuga, Milton Carlos [UNESP]; Tormin, Fernanda Borges Cunha [UNESP]; Faria, Gisele [UNESP] (Wiley, 2017)
The aim was to evaluate the cytocompatibility of the AH Plus and Sealapex associated with amoxicillin (AA) in a quantity of 10% by total weight of the sealers, the flow and setting time of these sealers with 10%-0.25% AA and antibiofilm activity of these sealers associated with AA in a concentration that does not alter their physical properties (1%). Cytocompatibility was assessed by MTT, neutral red and cytoskeletal fluorescence assays. Setting time and flow was evaluated using the specifications of ISO 6876/2012. For the antibiofilm evaluation, materials were placed in direct contact with E. faecalis biofilm induced on dentin blocks. The incorporation of AA into the sealers did not diminish the viability of the fibroblasts and did not cause structural changes in the cytoskeletal. The flow of AH Plus + AA at 1.0; 0.5 and 0.25%, and of Sealapex + AA at 5.5; 2.5; 1.0; 0.5 and 0.25% were within the specifications of the ISO 6876. AH Plus, and AH Plus + AA at 1.0; 0.50 and 0.25% presented a setting time of 730, 439, 455, and 474 min., respectively. Sealapex - pure or associated with AA did not set completely. The addition of 1% AA to the sealers did not increase their antibiofilm activity. It was concluded that the incorporation of 10% AA caused no toxic effects on fibroblasts, but harmed the physical properties. The addition of AA in concentration that does not affect the physical properties of the sealers did not increase their antibiofilm activity.
Keywords: antibacterial activity; antibiotic; cytotoxicity; endodontic sealer; physical properties